Cold spray as a powder metallurgy process for production of nickel aluminium bronze - Steven Camilleri; Tien Tran; Andrew Duguid; Kannoorpatti Narayanan Krishnan (PLoS ONE, 2025)
Nickel aluminium bronze (NAB) alloys are known for their excellent strength and corrosion resistance, making them suitable for maritime and industrial applications. NAB is producible by Powder Metallurgy (PM) but typically requires high compaction pressure. The objective of this study is to investigate the manufacturing of NAB using the cold spray additive manufacturing (AM) process and to compare its properties to those produced by traditional methods such as casting and PM. Cold spray is a solid-state coating technique that accelerates powdered metal and carrier gas to supersonic speeds, enabling bonding through plastic deformation. Binary aluminium bronze (AB) and NAB alloys were produced using powders by cold spraying powders into 3D printed parts, and heat treating the resulting parts. The AB alloy contained blended 9.9% aluminium alloy (Al6061) powder and copper powder, while the NAB alloy included 11% Al6061 powder, 5.8% nickel powder, 6.8% iron powder, and copper powder. Powders were mixed under controlled conditions and deposited using a LightSPEE3D printer and compressed air. Post-deposition heat treatments, such as homogenisation, aging, and/or hot isostatic pressing (HIP), were applied to enhance material properties. The results indicate that the cold spray process, combined with appropriate heat treatments, can produce NAB alloys with desirable microstructures containing fine κ phases and mechanical properties with above 280 MPa yield strength, above 500 MPa tensile strength and 20% elongation which are comparable to those achieved by traditional cast methods which yield strength of 240 MPa, tensile strength of 580 MPa and 15% elongation, and superior to PM methods. This study demonstrates the viability of cold spray AM to enhance the production of complex high-strength alloys, offering significant advancements for maritime and industrial applications.